الوحدة الموضوعية في قصص سورة البقرة عند الإمام البقاعي السمع والطاعة أنموذجًا - مسناوتي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study is based on the thematic unity in the stories of surat al Baqarah from the views of al Imam al Biqa'i: Hearing and Obedience as a Model. The research examines stories of surat al Baqarah to highlight the approach of al Imam al Biqa'i in his dealings with the thematic unity in terms of hearing and obedience. This research aims: firstly, to identify the concept of the thematic unity, demonstrate its importance and types, and expose its relationship with the other sciences of the Qur'an, Secondly, to clarify the meaning of the hearing and obedience, demonstrates its importance and types and show the impacts of the hearing and obedience, Thirdly, it emphasizes the purposes of surat al Baqarah according to Imam al Biqa'i, describes his approach in dealing with the thematic unity and the purposes in surat al Baqarah through his tafsir. Fourly, it look into to the applicability of the thematic unity through the theme of the hearing and obedience. The researcher used inductive method the stories related to surat al Baqarah, which are presented by al Imam al Biqa'i' in his tafsir, and then compared them to the classical and modern tafsir books. The researcher also used the analytical method to analyse the views of al Imam al Biqa'i in relation to his argumentation on the thematic unity in the stories of surat al Baqarah. The research found that the thematic unity is a strong topic that collects the varieties of themes, in a single sura relating to challenges of modern life.